REVIEW PROSPEK FITOREMEDIASI LAHAN TERKONTAMINASI LOGAM BERAT DARI INDUSTRI KERTAS - Henggar Hardiani (Jurnal Ecolab, 2007)
Deinking process in paper industry is one of the industry which resulting toxic waste that containing heavy metals such as Pb, Cr,Cu,Ni,Cd and Hg originates from the ink dissolved in waste water. If improperly manage, these heavy metal will contaimine to the water and soil in environment. to reduce the heavy metal pollution, a Phytoremediation methode can be used as one option. in remediation process, the plant can absorb, degrade, transform, and immobilized the heavy metal. since indonesia is atropical country and has diversived plant biology, assesment on role of the plant contributing phytoremediation can be selected as technologygiving profit. based on some literatures, this study tried to explain the basic of phytoremediation and the mechanism of heavy metal absorption.